Excretory Urographic Renal findings in children with Severe Vesico-ureteric Reflux: A prospective study of operative versus non operative management. - Ahmed, Taskeen; Bilal, Hazrat; Rahman, Khalil ur; Rehman, Amir (Journal of Postgraduate Medical Institute, 2011)
thirty one children (7 boys, and 24 girls) were studied in a prospective trial of operative versus non-operative treatemtn in children with severe vesico ureteric reflux and urinary tract infection over 5 years period. Renal findings on excretory urography (EU) are reported Random allocation, of 16 chioldren to medical and 15 to surgical management, was done fifteen (48%) had confirmed renal scarring (8 medical, 7 surgical) at entry. Children with normal kidneys (8), areas of parenchymal thining (8) were also found. Follow - up EU was planned at 6, 18 and 54 months and urine culture, 99m technetium dimeracaptosuccinic acid scans and serum creatinine were evaluated. This observation was taken in 26 children (84%). Renal growth, with no alteration in morphology, was in managed medically and 3 surgically, there was development of new renal scars, including 2 formerly normal kidneys (1 medical, 1 Surgical). This occured in1 child after no operative treatment regarding the development of new renal scars and areas of thining or the progression of confirmed renal scars.